A 3D Printer Guide for the Development and Application of Electrochemical Cells and Devices - Silva, Ana Luisa; Salvador, Gabriel Maia da Silva; Castro, Sílvia V. F.; Carvalho, Nakédia M. F.; Munoz, Rodrigo A. A. (Frontiers in Chemistry, 2021)
3D printing is a type of additive manufacturing (AM), a technology that is on the rise and works by building parts in three dimensions by the deposit of raw material layer upon layer. In this review, we explore the use of 3D printers to prototype electrochemical cells and devices for various applications within chemistry. Recent publications reporting the use of Fused Deposition Modelling (FDM®) technique will be mostly covered, besides papers about the application of other different types of 3D printing, highlighting the advances in the technology for promising applications in the near future. Different from the previous reviews in the area that focused on 3D printing for electrochemical applications, this review also aims to disseminate the benefits of using 3D printers for research at different levels as well as to guide researchers who want to start using this technology in their research laboratories. Moreover, we show the different designs already explored by different research groups illustrating the myriad of possibilities enable by 3D printing.